2015
DOI: 10.1111/jth.12872
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin therapy is associated with less compact fibrin networks and enhanced fibrinolysis in patients with abdominal aortic aneurysm

Abstract: Scott DJA, Ajjan RA. Aspirin therapy is associated with less compact fibrin networks and enhanced fibrinolysis in patients with abdominal aortic aneurysm. J Thromb Haemost 2015; 13: 795-801.Summary. Objective: Thrombotic changes in fibrin networks contribute to increased cardiovascular risk in patients with abdominal aortic aneurysm (AAA). Given that aspirin modulates the fibrin network, we aimed to determine if aspirin therapy is associated with changes in ex-vivo fibrin clot characteristics in AAA patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…11 Indeed, inhibition of both isotypes as with aspirin not only decrease inflammation, but has also been reported to reduce the formation of fibrin networks that stabilize AAA thrombus via fibrinolysis. 12,13 Our findings support other studies which have illustrated the importance between thrombus, antiplatelet activity, and aneurysm growth. In an observational study, AAA expansion rate for patients on low-dose aspiring was significantly less in mm/year as compared to non-users.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11 Indeed, inhibition of both isotypes as with aspirin not only decrease inflammation, but has also been reported to reduce the formation of fibrin networks that stabilize AAA thrombus via fibrinolysis. 12,13 Our findings support other studies which have illustrated the importance between thrombus, antiplatelet activity, and aneurysm growth. In an observational study, AAA expansion rate for patients on low-dose aspiring was significantly less in mm/year as compared to non-users.…”
Section: Discussionsupporting
confidence: 90%
“…11 Indeed, inhibition of both isotypes as with aspirin not only decrease inflammation, but has also been reported to reduce the formation of fibrin networks that stabilize AAA thrombus via fibrinolysis. 12,13…”
Section: Discussionmentioning
confidence: 99%
“…564 Moreover, the use of aspirin or P2Y12 inhibitors has been associated with a reduced rate of death among patients with AAA. 428 In a study of the potential mechanisms underlying the benefits of aspirin therapy, Bailey and colleagues 565 showed that aspirin therapy in patients was associated with enhanced fibrinolysis and less compact fibrin networks. In a metaanalysis of a few trials, the use of aspirin was associated with lower expansion rates and less need for later surgical repair in patients with larger AAA ( > 35 mm).…”
Section: Platelet Inhibitorsmentioning
confidence: 99%
“…Several mechanisms appear to be involved including reducing tissue factor production by platelets and immune cells with the acetylation of thrombin and prothrombin also playing an important role [ 172 ] (reviewed by Undas et al [ 173 ]). In addition, high dose aspirin (greater than 300 mg/day) appears to increase the efficiency of fibrinolysis [ 174 , 175 ]. Ingestion of aspirin also leads to the upregulation of lipoxin A4 in humans and animals [ [176] , [177] , [178] , [179] ] via a mechanism involving the irreversible acetylation of COX2 [ 180 , 181 ] (reviewed by Romano et al [ 182 ]).…”
Section: Suggestions For Therapeutic Interventionmentioning
confidence: 99%